2018
DOI: 10.1039/c7ra13672b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of room temperature vulcanized silicone rubber based on rosin-grafted polydimethylsiloxane

Abstract: Rosin-grafted polydimethylsiloxane (RGSO) was prepared via ring-opening reaction of glycidyl ester of rosin acid (ER) with hydroxy-terminated amino polydimethylsiloxane (PDMS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…RA are composed of hydrophenanthrene structure and contains two chemically reactive centres in the molecule–the carbon-carbon double bonds and the carboxyl group. Therefore, RA can be chemically modified by esterification, isomerization, Diels-Alder addition, amidation reactions ( Figure 3 ) [ 33 , 34 ]. The bulky hydrophenanthrene group present in RA can significantly alter the thermal properties of polymers.…”
Section: The Use Of Tall Oilmentioning
confidence: 99%
See 2 more Smart Citations
“…RA are composed of hydrophenanthrene structure and contains two chemically reactive centres in the molecule–the carbon-carbon double bonds and the carboxyl group. Therefore, RA can be chemically modified by esterification, isomerization, Diels-Alder addition, amidation reactions ( Figure 3 ) [ 33 , 34 ]. The bulky hydrophenanthrene group present in RA can significantly alter the thermal properties of polymers.…”
Section: The Use Of Tall Oilmentioning
confidence: 99%
“…After converting the RA to RA glycidyl ester, the ring-opening reaction is performed using with hydroxy-terminated amino polydimethylsiloxane. The silicone rubber containing RA showed better thermal stability and mechanical properties compared to unmodified silicone rubber due to the strong rigidity and polar hydrogenated phenanthrene ring structure of RA [ 34 ].…”
Section: The Use Of Tall Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosin-modified room-temperature-vulcanized silicone rubber can be prepared from rosin glycidyl ester, aminopropyltrietoxysilane, tetraetoxysilane and hydroxyl-terminated polydimetoxysilane according to Scheme 72 [254]. Rosin-modified silicones shows significantly better thermal and mechanical properties in comparison with unmodified silicone [254,255,256].…”
Section: Rosin-based Chemicalsmentioning
confidence: 99%
“…With the depletion of fossil resources, biomass materials, as an upgraded substitute for petroleum-based compounds, have been widely used in the modification of silicone rubber [11][12][13]. Biomass materials containing rigid structures, such as cellulose, rosin, and dopamine, can cultivate composites with high mechanical properties and thermal stability [14][15][16]. Yang et al reported the mechanical reinforcement of RTV silicone rubber using modified cellulose nanocrystals as cross-linker and nanofiller [17].…”
Section: Introductionmentioning
confidence: 99%